2021
DOI: 10.1126/science.abb9303
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evolution of pain-inducing defensive venom components in spitting cobras

Abstract: Convergent evolution provides insights into the selective drivers underlying evolutionary change. Snake venoms, with a direct genetic basis and clearly defined functional phenotype, provide a model system for exploring the repeated evolution of adaptations. While snakes use venom primarily for predation, and venom composition often reflects diet specificity, three lineages of cobras have independently evolved the ability to spit venom at adversaries. Using gene, protein, and functional analyses, we show that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
125
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(154 citation statements)
references
References 117 publications
11
125
0
3
Order By: Relevance
“…Cytotoxic three-finger toxins (3FTxs) from N. atra and N. kaouthia venoms have been demonstrated to lyse erythrocytes [ 26 ], while the cytotoxic 3FTx complex hemextin AB identified from the venom of the closely related species Hemachatus haemachatus has been shown to inhibit the activity of the coagulation component factor VIIa [ 27 ]. The apparent synergy between PLA 2 s and 3FTxs in N. mossambica and H. haemachatus venom has been found to increase the potency of haemolytic venom activity [ 28 ], and perhaps cytolysis in general [ 29 ]. Some snake venom serine proteases (SVSPs), though not typically a major constituent of elapid venoms [ 30 ], can contribute to coagulant activity through the activation of clotting factors V/Va and VIII/VIIIa, thereby acting in a procoagulant manner [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytotoxic three-finger toxins (3FTxs) from N. atra and N. kaouthia venoms have been demonstrated to lyse erythrocytes [ 26 ], while the cytotoxic 3FTx complex hemextin AB identified from the venom of the closely related species Hemachatus haemachatus has been shown to inhibit the activity of the coagulation component factor VIIa [ 27 ]. The apparent synergy between PLA 2 s and 3FTxs in N. mossambica and H. haemachatus venom has been found to increase the potency of haemolytic venom activity [ 28 ], and perhaps cytolysis in general [ 29 ]. Some snake venom serine proteases (SVSPs), though not typically a major constituent of elapid venoms [ 30 ], can contribute to coagulant activity through the activation of clotting factors V/Va and VIII/VIIIa, thereby acting in a procoagulant manner [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, snake venom metalloproteinases (SVMPs) from N. naja venom have been found to cause delays in clotting time through the hydrolysis of haemoglobin [ 33 ]. However, in combination, 3FTxs, PLA 2 s and SVMPs typically account for >95% of the total toxin content of the majority of cobra venoms [ 29 ], and thus identifying the key toxins responsible for anticoagulant venom effects remains challenging. Nonetheless, a recent study showed that the PLA 2 inhibitor varespladib was capable of effectively neutralising the anticoagulant activity of many Afro-Asian elapids, including N. nigricollis [ 34 ], suggesting that this toxin family may be of greatest importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venom has independently evolved over 100 times across the Tree of Life, amounting to more than 200,000 species which use this protein and peptide mixture for prey capture and predator defense [ 1 , 2 , 3 , 4 ]. Snakes have evolved several different venom delivery systems primarily for prey capture [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a large sample of envenomations by a wide range of snakes, and the assumption that defensive venoms should invoke early pain to deter predators before damage is inflicted, Ward-Smith et al [ 19 ] tested the hypothesis that the defensive function has been important in venom evolution. They found no evidence that defense has been a pervasive influence in the evolution of venom in snakes overall, although interesting exceptions present fruitful avenues for further research [ 20 ].…”
mentioning
confidence: 99%